Nível de degradação termomecânica e coleta de compostos orgânicos voláteis durante a extrusão de polímeros - Coaquira, Carlos Alberto Cáceres (Universidade Federal de São Carlos, 2008)
In this work we studied the thermomechanical degradation and volatile organic compound (VOC) generated during extrusion of the HDPE, PP, and PS. The degradation processes occurred during extrusion were analyzed by a new methodology proposed in this work and called Degradation Level Distribution Function (DLDF). The results obtained were also correlated with the Chain Scission Distribution Function (CSDF) methodology previously proposed. Through DLDF methodology we can also find the critical molar mass ( c M ) above which the chain scission mechanism becomes predominant. The results showed that the chain scission process for HDPE and PP above c M is of a preferential type and random for the PS. The c M present a linear correlation with the weight average molecular weight and decreases with the increase of the extrusion temperature. The VOC generated during extrusion was analyzed via infrared spectroscopy and size exclusion chromatography. The results showed that these VOC are product of the degradation of polymer and additives. The molar mass of the VOC s varies between 100 to 1000 g/mol. The loss in weight for the volatilization of the material during extrusion is dependent of the polymer type and extrusion temperature. In the case of the PS the values vary between 25 and 850ppm and in the case of the HDPE and PP the loss is below 100ppm.
Degradation level of polymers and collection of volatile organic compounds during extrusion
Keywords: Polímeros; Degradação; Processo de extrusão; Cisão de cadeia; Compostos orgânicos voláteis; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS